GLUTAMINE AUGMENTS NEURONAL NETWORK ACTIVITY IN RAT HIPPOCAMPAL SLICES - Rehman, Mujeeb ur; Mushtaq, Muhammad; Sherkheli, Muhammad Azhar (Journal of Ayub Medical College Abbottabad, 2017)
Background: In recent past, a huge number of in vitro electrophysiological techniques have been developed to explore underlying mechanisms of most complicated functions of brain. Neurophysiologist and neuroscientist use different compositions of artificial cerebrospinal fluid (aCSF) usually based on ionic and energy demands of neurons but these compositions lack amino acids such as aspartic acid, taurine and glutamine. Methods: We used in vitro electrophysiological recording technique to estimate the effects of glutamine, an amino acid and precursor of neurotransmitters glutamate and GABA, on hippocampal sharp wave ripple activity (SPW-R) in rats. We evoked SPW-Rs in hippocampal slices applying high frequency stimulation. Results: We found that glutamine significantly enhanced the incidence and amplitude of sharp wave ripples. However, duration of sharp wave and ripples’ frequency did not change significantly. It is interesting that glutamine neither prolonged sharp wave ripple activity nor transformed these into pathological events such as recurrent epileptiform discharges. Conclusion: Our data indicate that addition of glutamine in aCSF may optimize the experimental conditions for in vitro electrophysiology without disturbing excitatory - inhibitory balance. This study may provide a better experimental paradigm for exploring the underlying mechanisms of neurological disorders and for searching new therapeutic options to cure these neurological conditions. Keywords: Hippocampus; SPW-Rs; Glutamine; CA3; CA1